The Culture of Power and Governance of Pakistan 1947-2008 - Ilhan Niaz (Karachi Oxford University Press, 2010)
This book attempts to explain Pakistan's crisis of governance in historical and philosophical terms. It argues that South Asia's indigenous orientation towards the exercise of power has reasserted itself and produced a regression in the behaviour of the ruling elite. This has meant that in the sixty years of independence from British rule the behaviour of the state apparatus and political class has become more arbitrary, proprietorial and delusional. The resulting deterioration in the intellectual and moral quality of the state apparatus is a mortal threat to Pakistan. Regrettably, much of the academic and public discussion about developing societies has been vitiated by the heedless repetition of fashionable jargon that emphasizes national security, democracy and development. The Culture of Power and Governance of Pakistan draws upon the primary declassified record of Pakistan and a diverse array of theoretical inputs to try and balance the debate on the crisis of governance
Include Bibliography and Index
Keywords: Pakistan Politics and Government. -- Civil-Military Relations Pakistan -- Bureaucracy